ANALISIS LITERASI KEUANGAN PEDAGANG DI PASAR OESAPA KOTA KUPANG NUSA TENGGARA TIMUR - Voldiana Sine; Pius Bumi Kellen; Paulina Yuritha Amtiran (Jurnal Ekobis : Ekonomi Bisnis & Manajemen, 2020)
This research aims to analyze the literacy levels of Oesapa Market traders. This research is a quantitative descriptive by using survey method. There are four indicators that used in this research, that indicators are: 1) Financial Knowledge,2) Financial Behaviour, 3) Financial attitudes and 4) Banking Technology. The population in this study was all traders in Oesapa Market and the sample in the study were 90 respondents from the entire population. Primary data were obtained from respondents by using questionnaires and direct interview with each respondents. The result of this research shows that literacy level of Oesapa Market traders be in moderate level which is for financial knowledge, financial behaviour and financial attitude be in moderate level, while banking technology conception in low levels. But for totality literacy level is moderat, it means that Oesapa Market traders have a knowledge and belief to Financial institution but they are not skilful to use products/services of financial institution.